2014
DOI: 10.1001/jama.2014.16819
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Multiple Micronutrient vs Iron–Folic Acid Supplementation on Infant Mortality and Adverse Birth Outcomes in Rural Bangladesh

Abstract: clinicaltrials.gov Identifier: NCT00860470.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
173
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 124 publications
(177 citation statements)
references
References 46 publications
(21 reference statements)
3
173
0
Order By: Relevance
“…115 In Bangladesh, antenatal multiple micronutrient with the same formulation as used in Indonesia versus IFA supplementation had no effect on all-cause infant mortality in boys but lowered mortality in girls by 16%. 87 In this study, the investigators suggested that a larger birth size for boys might have differentially increased the risk of dying from asphyxia in the first few days after birth, which was not seen in girls. 87 Consequently, antenatal micronutrient supplementation might improve survival among offspring but the effect is likely to be modulated by local nutrition, disease and health care conditions.…”
Section: Antenatal Effects Across the Lifespanmentioning
confidence: 68%
See 4 more Smart Citations
“…115 In Bangladesh, antenatal multiple micronutrient with the same formulation as used in Indonesia versus IFA supplementation had no effect on all-cause infant mortality in boys but lowered mortality in girls by 16%. 87 In this study, the investigators suggested that a larger birth size for boys might have differentially increased the risk of dying from asphyxia in the first few days after birth, which was not seen in girls. 87 Consequently, antenatal micronutrient supplementation might improve survival among offspring but the effect is likely to be modulated by local nutrition, disease and health care conditions.…”
Section: Antenatal Effects Across the Lifespanmentioning
confidence: 68%
“…87 In this study, the investigators suggested that a larger birth size for boys might have differentially increased the risk of dying from asphyxia in the first few days after birth, which was not seen in girls. 87 Consequently, antenatal micronutrient supplementation might improve survival among offspring but the effect is likely to be modulated by local nutrition, disease and health care conditions. Unknown at present is the potential for preconceptional micronutrient interventions to affect survival of offspring during gestation and postnatally, which are effects requiring adequately sized population-based randomized trials with extended postnatal follow-up.…”
Section: Antenatal Effects Across the Lifespanmentioning
confidence: 68%
See 3 more Smart Citations